The suitability of atmospheric oxygen measurements to constrain western European fossil-fuel CO2 emissions and their trends - Rödenbeck, Christian; Adcock, Karina E.; Eritt, Markus; Gachkivskyi, Maksym; Gerbig, Christoph; Hammer, Samuel; Jordan, Armin; Keeling, Ralph F.; Levin, Ingeborg; Maier, Fabian; Manning, Andrew C.; Moossen, Heiko; et al. (Atmospheric chemistry and physics, 2023)
Atmospheric measurements of the O2/N2 ratio and the CO2 mole fraction (combined into the conceptual tracer “Atmospheric Potential Oxygen”, APO) over continents have been proposed as a constraint on CO2 emissions from fossil-fuel burning. Here we assess the suitability of such APO data to constrain anthropogenic CO2 emissions in western Europe, with particular focus on their decadal trends. We use an inversion of atmospheric transport to estimate spatially and temporally explicit scaling factors on a bottom-up fossil-fuel emissions inventory. Based on the small number of currently available observational records, our CO2 emissions estimates show relatively large apparent year-to-year variations, exceeding the expected uncertainty of the bottom-up inventory and precluding the calculation of statistically significant trends. We were not able to trace the apparent year-to-year variations back to particular properties of the APO data. Inversion of synthetic APO data, however, confirms that data information content and degrees of freedom are sufficient to successfully correct a counterfactual prior. Larger sets of measurement stations, such as the recently started APO observations from the Integrated Carbon Observation System (ICOS) European research infrastructure, improve the constraint and may ameliorate possible problems with local signals or with measurement or model errors at the stations. We further tested the impact of uncertainties in the O2:CO2 stoichiometries of fossil-fuel burning and land biospheric exchange and found they are not fundamental obstacles to estimating decadal trends in fossil-fuel CO2 emissions, though further work on fossil-fuel O2:CO2 stoichiometries seems necessary.
Im Titel ist "2" tiefgestellt
Online veröffentlicht: 22. Dezember 2023
Gesehen am 15.01.2025